2010
DOI: 10.1007/s11517-010-0621-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of biomechanical changes after removal of instrumentation in lumbar arthrodesis by finite element analysis

Abstract: The purpose of this study is to investigate the change in biomechanical milieu following removal of pedicle screws in instrumented single level lumbar arthrodesis. Using a validated finite element (FE) model of the intact lumbar spine (L2-5), two scenarios of L3-4 lumbar fusion were simulated: posterolateral fusion (PLF) at L3-4 using pedicle screws (PLF with pedicle screws; WiP) and L3-4 lumbar posterolateral fusion state after removal of pedicle screws (PLF without pedicle screws; WoP). The WiP model had gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 31 publications
1
43
0
1
Order By: Relevance
“…A pure moment of 10 Nm combined with a pre-compressive load of 150 N [19], [21][23] was applied to the top surface of T9. Flexion, extension, left/right lateral bending, and left/right axial rotation were simulated.…”
Section: Methodsmentioning
confidence: 99%
“…A pure moment of 10 Nm combined with a pre-compressive load of 150 N [19], [21][23] was applied to the top surface of T9. Flexion, extension, left/right lateral bending, and left/right axial rotation were simulated.…”
Section: Methodsmentioning
confidence: 99%
“…However, even though many previous studies have reported excellent surgical results with instrumented lumbar fusion for degenerative lumbar disease,1,3,4 the robust stiffness of pedicle screws and rods might lead to an increase in the stress concentration at the adjacent segment after fusion, which could be a candidate risk factor for adjacent segment degeneration (ASD) 5,6,7,8…”
Section: Introductionmentioning
confidence: 99%
“…Unilateral instrumentation has advantages over bilateral fixation in terms of reduced operation time, medical expenses, blood loss, and hospital stay duration 10,11. Furthermore, unilateral pedicle screw fixation can lead to a decrease in fusion segment stiffness and stress of facet joint at superior adjacent segment 5,16. From this perspective, unilateral pedicle screw fixation would have a positive effect on stress concentration at the adjacent segment after lumbar fusion surgery, which seems to be a potential benefit of unilateral fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Durchgeführt wurden diese im Mittel nach 10 (6-13) Monaten, bei 25% (0-100%) in einer minimal-invasiven Technik. Eine aktuelle Finite-Elemente-Analyse konnte zeigen, dass eine Entfernung der Instrumentierung die Steifigkeit eines fusionierten Segments verringert und so den Stress auf die benachbarten Bandscheiben vermindert [25].…”
Section: Implantatentfernung Nach Instrumentierungen An Der Wirbelsäuleunclassified